The Long Goodbye: Wealth Concentration in Italy 2002-2012 - Ignazio Drudi; Giorgio Tassinari (Statistica, 2015)
The paper illustrates the changes in family assets between 2002 and 2012, and measures the changes in the degree of inequality using Gini coefficient. Futhermore we try to identify which social groups  (classes) have gained by these changes, using the decomposition procedure of the Gini concentration ratio proposed by Dagum. The results show that the Great Recession has mainly manifested itself as an increase in the concentration of family assets, whch grows much more than income concentration. The dispersion of values of the assets within social groups has increased, and at the same time so has the transvariation between distributions.